Tree-Adjunct Grammatical Evolution - GALVAN-LOPEZ, EDGAR (IEEE Press, 2010)
In this paper we investigate the application of tree-adjunct grammars to grammatical evolution. The standard type of grammar used by grammatical evolution, context-free grammars, produce a subset of the languages that tree-adjunct grammars can produce, making tree-adjunct grammars, expressively, more powerful. In this study we shed some light on the effects of tree-adjunct grammars on grammatical evolution, or tree-adjunct grammatical evolution. We perform an analytic comparison of the performance of both setups, i.e., grammatical evolution and tree-adjunct grammatical evolution, across a number of classic genetic programming benchmarking problems. The results firmly indicate that tree-adjunct grammatical evolution has a better overall performance (measured in terms of finding the global optima).
Proceedings of the 12th Annual Congress on Evolutionary Computation
CEC 2010: 12th Annual Congress on Evolutionary Computation
PUBLISHED
Barcelona, Spain
Keywords: Applied mathematics; classic genetic programming; Genes & Society